Industrial chicory genome gives insights into the molecular timetable of anther development and male sterility - Waegneer, Evelien; Rombauts, Stephane; Baert, Joost; Dauchot, Nicolas; De Keyser, Annick; Eeckhaut, Tom; Haegeman, Annelies; Liu, Chang; Maudoux, Olivier; Notté, Christine; Staelens, Ariane; Van der Veken, Jeroen; et al. (Frontiers in Plant Science, 2023)
Industrial chicory (Cichorium intybus var. sativum) is a biannual crop mostly cultivated for extraction of inulin, a fructose polymer used as a dietary fiber. F1 hybrid breeding is a promising breeding strategy in chicory but crucially relies on stable self-incompatibility. Here, we report the assembly and annotation of a new industrial chicory reference genome. Additionally, we performed RNA-Seq on subsequent stages of flower bud development of a fertile line and two cytoplasmic male sterile (CMS) clones. Comparison of fertile and CMS flower bud transcriptomes combined with morphological microscopic analysis of anthers, provided a molecular understanding of anther development and identified key genes in a range of underlying processes, including tapetum development, sink establishment, pollen wall development and anther dehiscence. We also described the role of phytohormones in the regulation of these processes under normal fertile flower bud development. In parallel, we evaluated which processes are disturbed in CMS clones and could contribute to the male sterile phenotype. Taken together, this study provides a state-of-the-art industrial chicory reference genome, an annotated and curated candidate gene set related to anther development and male sterility as well as a detailed molecular timetable of flower bud development in fertile and CMS lines.